The first results of combined treatment of giant cell tumor of bone - A. A. Barashev; V. V. Mozulyaka; T. V. Ausheva; Yu. R. Vinnik; L. N. Vashchenko; E. M. Nepomnyashchaya; P. V. Chernogorov (Южно-Российский онкологический журнал)
Purpose of the study. To evaluate the effectiveness and possibility of wide clinical use of denosumab in neoadjuvant mode in patients with giant-cell bone tumors to simplify the operation by reducing the size of the tumor, consolidating pathological fractures, improving the quality of life, restoring the function of adjacent joints, by conducting 2 courses of denosumab as neoadjuvant targeted therapy for patients with giant-cell bone tumors, as well as evaluating morphological changes in tumor.Materials and methods. Considering the data on the efficacy of denosumab, all 10 patients underwent 2 courses of Denosumab 120 mg subcutaneously 1 time per month, as a neoadjuvant targeted therapy for a giant cell bone before performing a surgical treatment. The morphological picture was analyzed before and after the start of treatment, and the clinical and radiological results were evaluated.Results. A similar clinical picture was observed in all 10 cases involving pain relief and restoration of support ability of the bone. X-ray changes demonstrated the development of sclerotic processes in the foci of lytic destruction. Consolidation of pathological fractures was observed. The main changes determining the clinical and radiological characteristics were associated with the morphological processes occurring in the tumor under the influence of denosumab. The morphological picture in the surgically removed bone samples was associated with the development of fibroscle-rotic processes leading to the consolidation of pathological fractures.The histological changes were assessed at the light-optical level. Tumor cells (osteoblasts and osteoclasts) were replaced with fibrous tissue of varying maturity. That is, a response to the therapy (pathomorphosis in the tumor) was observed under the action of denosumab.Conclusions. Denosumab in neoadjuvant targeted therapy for patients with giant cell bone tumors prior to surgical treatment allows reduction in tumor sizes and consolidation of pathological fractures. The functions of adjacent joints were restored during Denosumab treatment. Improvements in the quality of life of patients were registered. The clinical and radiological effect of the therapy corresponded to the morphological changes occurring in the tumor. All of the above made it easier to perform surgery.